White spot syndrome virus and Enterocytozoon hepatopenaei in shrimp farms in Costa Rica = Virus del síndrome de la mancha blanca y Enterocytozoon hepatopenaei en camarón de cultivo en Costa Rica - Peña Navarro, Nelson 1985-; Castro Vásquez, Ruth Mayela 1982-; Dolz, Gaby (2020)
Introduction. The white spot syndrome virus (WSSV) causes systemic destruction of ectodermal and mesodermal tissues in shrimp and can cause 100 % mortality. Enterocytozoon hepatopenaei (EHP) is an intracellular microsporidian that causes lysis of epithelial cells in hepatopancreatic tubules in shrimp. Objective. Detect the presence of WSSV and EHP in fifteen shrimp farms in the Gulf of Nicoya and the Central Pacific from Costa Rica. Materials and methods. Between January 2017 and July 2018 water during the filling process of the pond, postlarvae, and juvenile shrimp of Penaeus vannamei was collected, during a production cycle in each one of the fifteen farms. Samples were analyzed through polymerase chain reaction (PCR) using primers and protocols to detect the VP41B gene in WSSV, and the small subunit ribosomal RNA gene of EHP. Results. The presence of WSSV was detected in one farm, while EHP was not detected in any of the fifteen farms. The sequencing of the amplified segments of the VP41B gene showed 100 % identity with isolated shrimp sequences in Taiwan and Mexico. Conclusion. WSSV was detected at a very low frequency and EHP was not detected in this study. It is necessary to continue monitoring these agents in the country's shrimp farms.
Introducción. El virus del síndrome de la mancha blanca (WSSV) causa la destrucción sistémica de los tejidos ectodérmicos y mesodérmicos en los camarones y puede causar una mortalidad del 100 %. El Enterocytozoon hepatopenaei (EHP) es un microsporidio intracelular que ocasiona lisis de las células epiteliales en los túbulos hepatopancreáticos del camarón. Objetivo. Detectar la presencia de WSSV y EHP en camarones de quince granjas ubicadas en el Golfo de Nicoya y el Pacífico Central de Costa Rica. Materiales y métodos. Entre enero 2017 y julio 2018 se recolectó agua durante el proceso de llenado del estanque, postlarvas y camarones juveniles de Penaeus vannamei, durante un ciclo productivo en cada una de las quince fincas. Las muestras se analizaron a través de reacción en cadena de la polimerasa (PCR), utilizando cebadores y protocolos para detectar el gen VP41B de WSSV y el gen de ARN ribosomal de la subunidad pequeña del EHP. Resultados. Se detectó la presencia de WSSV en una finca, mientras que no se detectó EHP en ninguna de las quince fincas. Las secuencias de los segmentos amplificados del gen VP41B mostraron una identidad del 100 % con secuencias aisladas de camarón en Taiwán y en México. Conclusión. Hubo baja frecuencia de WSSV, mientras que el EHP no fue detectado en este estudio. Es necesario continuar monitoreando estos agentes en las granjas camaroneras del país.
En Revista Agronomía mesoamericana
Volumen 31, número 2 (mayo-agosto 2020)
Descripción basada en el contenido visto el 21 de agosto, 2023
También disponible en formatos EPUB, HTML y XML
Keywords: VIRUS DEL SÍNDROME DE LA MANCHA BLANCA; CAMARONES -- ENFERMEDADES; REACCION EN CADENA DE LA POLIMERASA; ENFERMEDADES INFECCIOSAS; PARASITOS